Software engineering and methodology for emerging domains : 15th National Software Application Conference, NASAC 2016, Kunming, Yunnan, November 3-5, 2016, Proceedings /: 15th National Software Application Conference, NASAC 2016, Kunming, Yunnan, November 3-5, 2016, Proceedings. (2016) - Unknown
No abstract available